Unraveling the Patterns of Complexity in Transnational Corporate Bribery - Chan, Fiona (International criminal justice review, 2024)
Scholarship on white-collar and corporate crime often notes that these crimes are complex due to their scale, longevity, and hidden, layered, and global nature. Embedded in these discursive descriptions is the assumption that complexity is unidimensional and operates solely in a linear fashion. Yet, corruption and transnational bribery are the results of a complex system that involves diverse actors interacting in dynamic environments, which can produce multiple classes of outcomes that may include different patterns of complexity in crime. In this paper, we empirically explore potential variability in patterns of complexity in transnational corporate bribery using official data from cases prosecuted under the Foreign Corrupt Practices Act in the United States. Our findings indicate that crime “complexity” can take different forms, suggesting that the relationship between variables can unfold in dynamic ways. Implications for theory and practice are discussed.